PENGARUH TRAINING, PENGEMBANGAN KARIER DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA PEGAWAI (Studi Kasus: Dppkad Di Pemprov Bangka-Belitung) - Harun, Efendi; Elmi, Farida (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
Departing from the phenomena in increasing the productivity of civil servants every local government fix themselves, which we know will automatically improve the productivity of regional quality. The purpose of this research is to know the effect of training, career development and incentives one by one or simultaneously (simultaneously) to productivity of employees of Revenue Service of Financial Management and Regional Asset of BangkaBelitung Province Government (DPPKAD). Type of quantitative research with explanatory. Population of all employees of DPPKAD Government of Bangka-Belitung Province, while sampling technique probability sampling with slovin formula, found 203 employees as respondents, data analysis using multiple linear regression that the result of training, career development and incentives have a significant effect on work productivity, so it is advisable to increase training to improve career development according to internal needs so that DPPKAD officials of Bangka-Belitung Provincial Government are increasingly innovating and willing to share ideas and ideas, while the incentive variable should receive special attention